The IL-20 Cytokine Family in Rheumatoid Arthritis and Spondyloarthritis - Kragstrup, Tue W.; Andersen, Thomas; Heftdal, Line D.; Hvid, Malene; Gerwien, Jens; Sivakumar, Pallavur; Taylor, Peter C.; Senolt, Ladislav; Deleuran, Bent (Frontiers in Immunology, 2018)
This review describes the IL-20 family of cytokines in rheumatoid arthritis (RA) and spondyloartrhitits (SpA) including psoriatic arthritis. The IL-20 receptor (R) cytokines IL-19, IL-20 and IL-24 are produced both in the peripheral blood and in the synovial joint and are induced by Toll-like receptor ligands and autoantibody associated immune complexes in monocytes. IL-19 seems to have anti-inflammatory functions in arthritis. In contrast, IL-20 and IL-24 increase the production of proinflammatory molecules such as monocyte chemoattractant protein 1 and are associated with bone degradation and radiographic progression. IL-22 is also associated with progression of bone erosions. This suggests that the IL-22RA1 subunit shared by IL-20, IL-22 and IL-24 is important for bone homeostasis. In line with this, the IL-22RA1 has been found on preosteoclasts in early RA. IL-26 is produced in high amounts by myofibroblasts and IL-26 stimulation of monocytes has been shown to be an important inducer of Th17 cells in RA. This indicates a role for IL-26 as an important factor in the interactions between resident synovial cells and infiltrating leukocytes. The strategy for modulating the IL-20 cytokine family should take into account the overlap in cellular sources and effector mechanisms. The redundancy encourages inhibition of more than one cytokine or one of the shared receptors. All IL-20 family members utilize the Janus kinase signaling pathway and are therefore potentially inhibited by drugs targeting these enzymes.